A Novel Long‐Range n to π* Interaction Secures the Smallest known α‐Helix in Water. (8th November 2019) - Hoang, Huy N.; Wu, Chongyang; Hill, Timothy A.; Dantas de Araujo, Aline; Bernhardt, Paul V.; Liu, Ligong; Fairlie, David P.
Abstract: The introduction of an amide bond linking side chains of the first and fifth amino acids forms a cyclic pentapeptide that optimally stabilizes the smallest known α‐helix in water. The origin of the stabilization is unclear. The observed dependence of α‐helicity on the solvent and cyclization linker led us to discover a novel long‐range n to π* interaction between a main‐chain amide oxygen and a uniquely positioned carbonyl group in the linker of cyclic pentapeptides. CD and NMR spectra, NMR and X‐ray structures, modelling, and MD simulations reveal that this first example of a synthetically incorporated long‐range n to π* CO⋅⋅⋅C γ =Ο interaction uniquely enforces an almost perfect and remarkably stable peptide α‐helix in water but not in DMSO. This unusual interaction with a covalent amide bond outside the helical backbone suggests new approaches to synthetically stabilize peptide structures in water. Abstract : Die kleinste bekannte α‐Helix in Wasser wird durch eine Amidbindung stabilisiert, die die Seitenketten der ersten und fünften Aminosäure in einem Pentapeptid verbindet. n→π*‐Wechselwirkungen zwischen einem Hauptketten‐Amidsauerstoff und einer Carbonylgruppe im Linker der cyclischen Pentapeptide wurden entdeckt. Die Charakterisierung zeigt, dass diese Interaktion die Peptid‐α‐Helix in Wasser, aber nicht in DMSO stabilisiert.